Poly (vinyl alcohol)/gum karaya electrospun plasma treated membrane for the removal of nanoparticles (Au, Ag, Pt, CuO and Fe3O4) from aqueous solutions - Padil, Vinod Vellora Thekkae; Černík, Miroslav (Journal of hazardous materials, 2015)
In the present work, nanofibre membranes composed of polyvinyl alcohol (PVA) and a natural gum karaya (GK) hydrocolloid were prepared using electrospinning. The electrospun membranes of PVA/GK were cross-linked with heat treatment and later methane plasma was used to obtain a hydrophobic membrane. The morphology, characterization and adsorption ability of P-NFM was assessed using scanning electron microscopy, UV-vis spectroscopy, ATR-FTIR techniques, water contact angle and ICP-MS analytical methods. The membrane was employed for the extraction of nanoparticles (Ag, Au, Pt, CuO and Fe3O4) from water. The nanoparticle extraction kinetic and adsorption isotherm perform the pseudo-second-order model and Langmuir isotherm model, respectively. The adsorption capacities of the membrane for the removal of NPs from water diverge in the order Pt>Au>Ag>CuO>Fe3O4. The high adsorption efficiency for the removal of NPs from water was compared with an untreated membrane. Physisorption, functional group interactions, complexation reactions between metal/metal oxide nanoparticles with various functional groups present in NFM and modified surface properties such as the balance of hydrophilicity/hydrophobicity, surface free energy, and the high surface area of the plasma treated membrane were possible mechanisms of NPs adsorption onto NFM. The regeneration and reusability were tested in five consecutive adsorption/desorption cycles.
Keywords: Metal Nanoparticles; termodynamika; Microscopy, Electron, Scanning; Nanofibers; Adsorption; guma karaya; mikroskopie elektronová rastrovací; polyvinylalkohol; nanovlákna; Water Pollutants; Thermodynamics; adsorpce; membrány umělé; Electrospinning; Membranes, Artificial; Kinetics; kovové nanočástice; Polyvinyl Alcohol; kinetika; Plasma treatment; látky znečišťující vodu; spektroskopie infračervená s Fourierovou transformací; Spectroscopy, Fourier Transform Infrared; Nanoparticles; PVA/GK nanofibre membrane; Karaya Gum